Exploring the role of Cdk5 on striatal synaptic plasticity in a 3-NP-induced model of early stages of Huntington’s disease - Hernández-Echeagaray, Elizabeth; Miranda-Barrientos, Jorge A.; Nieto-Mendoza, Elizabeth; Torres-Cruz, Francisco Miguel (Frontiers in Molecular Neuroscience, 2024)
Impaired mitochondrial function has been associated with the onset of neurodegenerative diseases. Specifically, certain mitochondrial toxins, such as 3-nitropropionic acid (3-NP), initiate cellular changes within the striatum that closely resemble the pathology observed in Huntington’s disease (HD). Among the pivotal signaling molecules contributing to neurodegeneration, cyclin-dependent kinase 5 (Cdk5) stands out. In particular, Cdk5 has been implicated not only in cellular pathology but also in the modulation of synaptic plasticity. Given its widespread presence in the striatum, this study seeks to elucidate the potential role of Cdk5 in the induction of corticostriatal synaptic plasticity in murine striatal cells subjected to subchronic doses of 3-NP in vivo, aiming to mimic the early stages of HD. Immunostaining analyses revealed an increase in Cdk5 in tissues from animals treated with 3-NP, without a significant change in protein levels. Regarding striatal plasticity, long-term depression (LTD) was induced in both control and 3-NP cells when recorded in voltage clamp mode. The Cdk5 inhibitor roscovitine-reduced LTD in most cells. A minority subset of cells exhibited long-term potentiation (LTP) generation in the presence of roscovitine. The inhibitor of D1 receptors SCH23390 prevented LTP in three of nine cells, implying that MSN cells lacking D1/PKA activation were capable of LTP induction when Cdk5 was also blocked. Nevertheless, the co-administration of H89, a PKA inhibitor, along with roscovitine, prevented the generation of any type of plasticity in all recorded cells. These findings show the impact of 3-NP treatment on striatal plasticity and suggest that Cdk5 during early neurodegeneration may attenuate signaling pathways that lead neurons to increase their activity.